Analisis Spasial Penyakit Kusta di Lampung - Sari, Nurhalina; Nurmala, Eliza Eka (Persatuan Dosen Kesehatan Masyarakat, 2019)
Leprosy is health problem because It appears morbidity and disablement that influences quality of life. Indonesia in 2020, declares to be leprosy free country in Bangkok Declaration 2013. But, until 2015, There is still the report of leprosy case, include Lampung. The research aims to spatial analysis for leprosy and the risk factor. It wants to get the priority area for handling the leprosy in Lampung.The research used ecology study design. Data of leprosy and the risk factor was gotten from secunder data: Central Bureau of Statistics and Public Health Office in Lampung 2011-2015. Data analysis used spatial analysis. Leprosy case was gotten in two category, pausibasiler (PB) and multibasiler (MB). From 15 regency, there was Pesisir Barat Regency that didn’t report leprosy case. Spatial result for 5 years reported the dominant leprosy case in Lampung Tengah and Lampung Timur Regency. In addition, It was found several regency that had higher risk to leprosy case in future. It based on population density, the number of poor people, sanitation, nutritional status and health facilities. A number of Regency were known to have higher risk to development of leprosy in the future. Spatial result can be used to decide priority area for handling the leprosy in Lampung.